AMF colonization and community of a temperate invader and co-occurring natives grown under different CO2 concentrations for 3 years. (7th July 2021) - Lu, Xiu-Rong; Feng, Wei-Wei; Wang, Wen-Jun; Chen, Ji-Xin; Sun, Jian-Kun; Qu, Bo; Liu, Ming-Chao; Feng, Yu-Long
Abstract: Global changes such as atmospheric CO2 enrichment often facilitate exotic plant invasions and alter soil arbuscular mycorrhizal fungi (AMF) community. However, it is still unclear whether the effects of CO2 enrichment on exotic plant invasions are associated with its effects on root-AMF symbiosis of invasive and native plants. To address this issue, the annual invasive plant Xanthium strumarium and two phylogenetically related annual natives were compared under ambient and elevated CO2 concentrations for three consecutive years. Atmospheric CO2 enrichment increased AMF colonization rates for the species only in few cases, and the invader did not benefit more from CO2 enrichment in terms of AMF colonization. Under ambient CO2 concentration, however, the invader had a higher AMF colonization rate than the natives in the first year of the study, which disappeared in the second and third year of the study due to the increase of AMF colonization rates in the natives but not in the invader. The influences of species, CO2 concentrations and planting year on AMF colonization were associated with their effects on both soil nutrient and AMF community, and the former may be more important as it also influenced the latter. Our results indicate that the invader could more quickly form symbiosis with soil AMF, contributing to adaptation and occupation of new habitats, and that it is necessary to consider the roles of AMF and the effects of time when determining the effects of global changes such as atmospheric CO2 enrichment on exotic plant invasions. Graphical Abstract: